Expression of recombinant surfactant protein SFTA3 in the human kidney cell line HEK 293T - Schröder, Henrik; Fischer, Ronny; Sollfrank, L.; Paulsen, Friedrich; Bräuer, Lars; Schicht, Martin (Annals of Anatomy-Anatomischer Anzeiger, 2017)
Pulmonary surfactant is broadly known to keep the lung dry, clean and open by lowering the surface tension of the fluid-film that lines the alveoli. The surfactant's protein component, the so called surfactant proteins (SPs), make up a multifunctional protein family. In addition to the four "classical" surfactant proteins (SP-A, SP-B, SP-C and SP-D), which possess immunologic as well as surfactant regulatory properties, two novel putative surfactant proteins (SFTA2 and SFTA3) have recently been described. Neither of them shows sequential nor structural similarity with the already known surfactant proteins. However, bioinformatic analyses as well as first molecular-biological studies reveal properties that have already been described for known surfactant proteins. In our present work we introduce a technique to synthesize, purify and stabilize recombinant SFTA3 derived from the human embryonic kidney cell line HEK 293T. This will provide investigators with a valuable source of further examination and characterization of this fascinating novel member of the surfactant protein family.
EVALuna2:34489